2021
DOI: 10.1007/s10529-021-03203-0
|View full text |Cite
|
Sign up to set email alerts
|

An uncharacterized protein from the metagenome with no obvious homology to known lipases shows excellent alkaline lipase properties and potential applications in the detergent industry

Abstract: A novel lipase, Lip486, which has no obvious homology with known lipases, was discovered using functional metagenomics technology. Phylogenetic tree analysis suggested that the enzyme belongs to a new subfamily called lipolytic enzyme family II. To explore the enzymatic properties, lip486 was expressed heterologously and e ciently in Escherichia coli. The recombinant enzyme displayed the highest activity on the substrate p-nitrophenyl caprate with a carbon chain length of 10, and its optimum temperature and pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The recombinant LipGt6 exhibited the highest activity towards medium-and longchain fatty acids (C8-C14). LipGt6 has 12.6% sequence similarity with the lipase Lip486 [17]. Both Lip29 and Lip486 are reported lipases that belong to the GDSL family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recombinant LipGt6 exhibited the highest activity towards medium-and longchain fatty acids (C8-C14). LipGt6 has 12.6% sequence similarity with the lipase Lip486 [17]. Both Lip29 and Lip486 are reported lipases that belong to the GDSL family.…”
Section: Discussionmentioning
confidence: 99%
“…At present, all lipases that can be added to detergents are alkaline, and their optimum pH is 8.0-12.0 [17]. An ideal lipase for detergent addition should have the following characteristics: high activity, high reaction temperature, high pH, and strong resistance to alkali substances, organic solvents, metal ions, and other chemical substances [18].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2018) reported an alkaline, low-temperature, and strong surfactant tolerance recombinant lipase of Trichoderma lentiform ACCC30425 in Pichia pastoris GS115; this lipase is suitable for use in the detergent industry. Xiao et al (2021) also reported a recombinant lipase Lip486 without clear homology alao to know lipase, Lip486 was discovered by using functional metagenomics technology and belongs to a new sub-familycalled lipolytic enzyme family II. The recombinant Lip486 expresses great activity and stability even in alkaline pH and medium-low temperature environments; these properties will make the lipase most important for use in detergent and other industries in the future.…”
Section: In Detergent Manufacturingmentioning
confidence: 99%
“…Unfortunately, in numerous instances, the characteristics of lipases (like other enzymes) do not meet the requirements of industrial catalysts, and their catalytic performance in industrial reactions is inadequate. Currently, there are numerous strategies to address some of the problems with lipases, using metagenomics (searching for beneficial enzymes) (Xiao et al 2021 ), site-directed mutagenesis (Maldonado et al 2023 ; Min et al 2021 ; Wang et al 2021a ), directed evolution (Li et al 2021 ), and chemical modification (Cavalcante et al 2022 ). Protein engineering strategies that utilize genetic mutation based on resolved lipase crystal structures can effectively modify lipase activity and stability (Lan et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%